Why Infertility Patients Came Late to Infertility Clinics (Study at Kariadi General Hospital) - Rahma Khusnul Khotimah; Besari Adi Pramono; Suharto Suharto; Yuli Trisetiyono (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2021)
Background: Infertility is an inability of a spouse to get pregnant within twelve months seeking pregnancy without using any contraception. The duration of infertility affects the chance to get pregnant.Objective: To identify the factors causing infertility patient came late to Polyclinic Merpati RSUP Dr. KariadiMethods: This study was an observational descriptive with a cross-sectional design. The data were obtained from medical records and questionnaires. Twenty-six respondents were infertility patients who met the inclusion and exclusion criteria and came to Polyclinic Merpati RSUP Dr. Kariadi in September 2020.Results: The number of infertility patients in September 2020 was 76 patients, 72,4% of them came to Polyclinic Merpati late. Most people came after being referred from the previous doctors. Three factors causing infertility patients came late were economic factors, a social factor, and another difficulty.Conclusion: Factors causing the late coming of infertility patients were economic factors, a social factor, and another difficulty